COOPERATION BETWEEN INDONESIA-PHILIPPINES ON COMBATING DRUGS IN ASEAN [KERJA SAMA INDONESIA-FILIPINA TERHADAP PEREDARAN NARKOTIKA DI ASEAN] - Yovan Gary Otniel; Avirell Felicia Kangmajaya (Universitas Pelita Harapan, 2020)
The cooperation between the Republic of Indonesia and the Republic of the Philippines in regards to combating the illicit drug trade signed in 2015 was an extension to the 2010 bilateral agreement to combat transnational organized crime. So far, this cooperation with the Republic of the Philippines hasn’t been successful in reducing the number of drugs being trafficked to Indonesia. Instead, Indonesia has shifted from being a transit hub to a lucrative market for the international illicit drug industry. Thus, this research is aimed to identify and analyze the reasons behind Indonesia’s decision to extend the latter in 2015 and the implementation of this new agreement with the Philippines in regards to Indonesia’s effort on combating the illicit drug trade in Southeast Asia. This research applies the qualitative descriptive approach in this research, especially on the concepts foreign policy and bilateral security cooperation, achieved through both literature studies and interviews. Results of the research showed that the continuous rise of Indonesia’s drug trafficking numbers and the profits being used as funding for other transnational criminal activities such as but not limited to terrorist groups, serves as the foundation behind Indonesia’s decision in its bilateral agreement of intelligent and best practice exchanges with the Republic of the Philippines in regards to combat drug trafficking, which has positively impact Indonesia’s capability on combating the illicit drug trade in the Association of Southeast Asian Nation (ASEAN). Bahasa Indonesia Abstract: Kerja sama antara Republik Indonesia dengan Republik Filipina berkaitan dengan upaya melawan perdagangan narkotika ilegal yang ditandatangani pada 2015 merupakan kelanjutan dari kesepakatan bilateral untuk melawan kejahatan transnasional yang terorganisir pada 2010. Sejauh ini, kerja sama dengan Republik Filipina tersebut masih belum berhasil mengurangi jumlah narkotika yang diperdagangkan secara ilegal di Indonesia. Bahkan, Indonesia justru beralih dari peran sebagai “terminal penghubung” menjadi pasar yang sangat menjanjikan bagi industry perdagangan narkotika ilegal. Sehingga, penelitian ini bertujuan untuk mengidentifikasi dan menganalisis alasan-alasan dibalik keputusan Indonesia untuk melanjutkan proses kerja sama pada 2015 serta implementasi dari kesepakatan baru dengan Filipina tersebut dikaitkan dengan upaya-upaya Indonesia dalam melawan perdagangan narkotika ilegal di Asia Tenggara. Penelitian ini mengaplikasikan pendekatan kualitatif deskriptif, terutama yang berkaitan dengan konsep kebijakan luar negeri dan kerja sama keamanan bilateral, yang dicapai melalui studi pustaka dan wawancara. Hasil dari penelitian ini menunjukkan bahwa peningkatan angka perdagangan narkotika ilegal di Indonesia yang berkelanjutan serta keuntungan yang digunakan sebagai pendanaan terhadap aktivitas kejahatan transnasional lainnya (terutama dan tidak terbatas kepada kelompok terorisme) adalah fondasi dibalik keputusan Indonesia terhadap kesepakatan bilateral dengan Republik Filipina di bidang pertukaran intelijen dan praktik terbaik sebagai upaya melawan perdagangan narkotika ilegal. Hal ini memberikan dampak yang positif terhadap kapabilitas Indonesia dalam melawan perdagangan narkotika ilegal di kawasan Asia Tenggara melalui ASEAN.